2008
DOI: 10.3748/wjg.14.720
|View full text |Cite
|
Sign up to set email alerts
|

Double balloon endoscopy associated pancreatitis: A description of six cases

Abstract: INTRODUCTIONSince its introduction in 2001 by Yamamoto [1] , double balloon endoscopy (DBE) has revolutionized both diagnostic and therapeutic small bowel endoscopy [2] . This technique allows (intervention) endoscopy of the complete small bowel (often in two sessions) with the possibility of carrying out interventions; e.g. mucosal biopsy, argon plasma coagulation, snare polypectomy, injection therapy, tattooing, foreign body extraction and balloon dilatation. DBE plays an important role in the diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
19
2
2
Order By: Relevance
“…Diagnostic DBE is accompanied by complications in < 1 % of cases. Hyperamylasaemia has been documented in up to 50 % of patients [157], but clinically significant pancreatitis occurs in only 1 %, almost exclusively after use of the oral insertion route [158,159]. Therapeutic balloon enteroscopy with balloon dilation of strictures has a reported perforation risk of 0 % -3 %, which is comparable to dilation of colonic Crohnʼs strictures [160,161].…”
Section: Balloon-assisted Enteroscopy (Bae)mentioning
confidence: 75%
“…Diagnostic DBE is accompanied by complications in < 1 % of cases. Hyperamylasaemia has been documented in up to 50 % of patients [157], but clinically significant pancreatitis occurs in only 1 %, almost exclusively after use of the oral insertion route [158,159]. Therapeutic balloon enteroscopy with balloon dilation of strictures has a reported perforation risk of 0 % -3 %, which is comparable to dilation of colonic Crohnʼs strictures [160,161].…”
Section: Balloon-assisted Enteroscopy (Bae)mentioning
confidence: 75%
“…In the series published to date, complications of DBE solely relating to the diagnostic procedure are rare. A recent retrospective multicenter survey in four countries has indicated a complication rate of 0.8% (13/1728) in diagnostic procedures and 4.3% (27/634) for therapeutic DBE, and there were no fatal cases [63,84,85] . During DBE, careful attention must be paid not to insufflate too much air, because this induces intestinal loop formation and impedes deep advancement [73] .…”
Section: Overall Experience Of Pjs Patientsmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50] Two large studies have reported on the complications associated DBE. 40,41 A large, multicenter international complication survey was presented by Mensink et al 40 A total of 10 centres across four continents were participated in the study and reported on a total of 40 complications in 2362 DBE procedures, 13 in 1728 diagnostic DBE (0.8%), and 27 during 634 therapeutic procedures (4.3%).…”
Section: Complications Of Double Balloon Enteroscopymentioning
confidence: 99%